Advancing the Development of Recyclable Aromatic Polyesters by Functionalization and Stereocomplexation. (19th February 2022) - Fan, Hua‐Zhong; Yang, Xing; Chen, Jia‐Hao; Tu, Yi‐Min; Cai, Zhongzheng; Zhu, Jian‐Bo
Abstract: The development of innovative synthetic polymer systems to overcome the trade‐offs between the polymer's depolymerizability and performance properties is in high demand for advanced material applications and sustainable development. In this contribution, we prepared a class of aromatic cyclic esters (M1 –M5 ) from thiosalicylic acid and epoxides by facile one‐pot synthesis. Ring‐opening polymerization of M s afforded aromatic polyesters P(M )s with high molecular weights and narrow dispersities. The physical and mechanical properties of P(M )s can be modulated by stereocomplexation and regulation of the side‐chain flexibility of the polymers, ultimately achieving high‐performance properties such as high thermal stability and crystallinity ( T m up to 209 °C), as well as polyolefin‐like high mechanical strength, ductility, and toughness. Furthermore, the functionalizable moieties of P(M )s have driven a wide array of post‐polymerization modifications toward access to value‐added materials. More importantly, the P(M )s were able to selectively depolymerize into monomers in excellent yields, thus establishing its circular life cycle. Abstract : The exploitation of epoxides as building blocks enabled the preparation of a series of recyclable aromatic polyesters with functionalizable moieties, which has driven a wide array of post‐polymerization modifications toward access of value‐added materials. Stereocomplexed polymers were formed with enhanced thermal stability and crystallinity, and random copolymers displayed polyolefin‐like mechanical performance.